07 A SIGNIFICANT DECLINE IN COLECTOMY RATES FOR COLORECTAL CANCER IN PATIENTS WITH ULCERATIVE COLITIS. (7th February 2019) - Picardo, Sherman; Seow, Cynthia; Novak, Kerri; Panaccione, Remo; Kaplan, Gilaad
Abstract: Background: Patients with ulcerative colitis (UC) are at increased risk of developing colorectal cancer. Independent risk factors include age, gender, extent and duration of disease activity, concurrent primary sclerosing cholangitis, a family history of sporadic colorectal cancer and severity of histologic bowel inflammation. Surveillance programs have been introduced to facilitate early detection of pre-malignant lesions, however, the efficacy of these programs have not been established. Technological endoscopic advancements and improved treatment options may also reduce the incidence of colorectal cancer in this population. Aims: To explore temporal trends in colectomy rates for colorectal cancer, in patients with ulcerative colitis. Methods: A population-based prevalent cohort of patients with ulcerative colitis (UC) from Alberta, Canada (2003-2015) was derived from administrative databases, based on a previously validated method. 1 The Discharge Abstract Database (DAD) was used to identify patients admitted for colectomy (Canadian Classification of Health Interventions procedure code (CCI): 1.NM.87, 1.NM.89, 1.NM.91, 1.NQ.89, 1.NQ.90) and with a diagnosis of colorectal cancer (International Classification of Disease -10 diagnosis code (ICD-10): C18.X (1-9), C19, C20.) Annual incidence was calculated by dividing the total number of colectomies for cancer by the at risk number of prevalent UC patients each fiscal year. Time trend analysis of colectomy rates for cancer was performed using a generalized linear model, assuming a Poisson distribution, using year of admission as the primary predictor, while adjusting for age and gender. Join-point regression was used to identify significant inflection points in temporal trends. Results: 112 patients with ulcerative colitis underwent a colectomy for colorectal cancer between 2003 and 2015, with an average annual colectomy rate of 1.32 per 1000 UC patients at risk. Average annual colectomy rates were higher in males and in increasing age categories. (Table 1) There was a significant reduction in colectomy rates over time. (IRR= 0.914, 95% CI: 0.868-0.961, p<0.001) (Figure 1) No significant inflection points were identified with join-point regression analysis. Conclusion: There has been a significant decline in colectomy rates for colorectal cancer in patients with ulcerative colitis, with an annual reduction of 8.6%, between 2003 and 2015. This is likely attributable to development and utilisation of surveillance programs and improvements in treatment options for patients with UC. Reference: 1. Rezaie A, Quan H, Fedorak RN, Panaccione R, Hilsden RJ. Development and validation of an administrative case definition for inflammatory bowel diseases. Canadian Journal of Gastroenterology 2012;26(10):711-717.